Electricity and Static: Franklin and his British compatriots - Robert Mankin (Transatlantica, 2010)
Franklin’s discoveries in electricity have rewarded scholarly attention for many decades. This short essay is not about electricity in the strict sense, but about the context in which Franklin presented some of his work in science and in politics in 1751, and about the way that work was received in Britain. The aim of the essay is to suggest that Franklin was neither a child of the British or European Enlightenment nor one of its toys. And though he may have been touted very generally as an inspiration, he was closer to a foreign force with which, intellectually as well as a politically, it had to contend. This may help in explaining why he proved so considerable a foe to the British state.